Modeling of the Fresh Fruit Bunches Collection and Transportation System with Agent-Based Simulation in Optimizing the Mode of Transportation on Oil Palm Industry - Rizkha Rida (Journal of Science Technology (JoSTec), 2023)
Uncertainty number of harvests per day causes the allocation of transportation modes are less optimal in collecting fruit from plantations to palm oil mills causing a shortage of trucks in some afdeling and some are unemployed in some afdeling causing large transportation costs. The use of Agent-Based Simulations can help to identify the factors that cause the number of trucks that are not optimal by looking at the behavior and interaction between the agent actors involved in the tbs collection and transportation process. The results showed the utilization rate of transportation modes increased from 27% to 40% by reducing the number of truck units rented from 177 trucks to 118 trucks and reducing transportation collection costs by 0.225% of the total cost value. With the reduced journey time, the quality of the oil palm is better with the reduction of free fatty acids (FFA) and the average weight loss of fruit.